2019
DOI: 10.1007/s40473-019-00186-1
|View full text |Cite
|
Sign up to set email alerts
|

Can Understanding Reward Help Illuminate Anhedonia?

Abstract: Purpose of Review The goal of this paper is to examine how reward processing might help us understand the symptom of anhedonia. Recent Findings There are extensive reviews exploring the relationship between responses to rewarding stimuli and depression. These often include a discussion on anhedonia and how this might be underpinned in particular by dysfunctional reward processing. However, there is no specific consensus on whether studies to date have adequately examined the various subcomponents of reward pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 80 publications
0
5
0
Order By: Relevance
“…As a prior metaanalysis suggested that both reward sensitivity and learning rate contribute to performance on the task (Huys et al, 2013), the specific aspects of reward processing that may be gauged by PRT performance remains an important topic for future research. Overall, while research has begun to explore links between subcomponents of reward processing and anhedonia, neurobiological processes through which anhedonia relates to subcomponents of reward remain undercharacterized (Kaya & McCabe, 2019;Treadway & Zald, 2011) | 1227 development efforts focused on reward processing (Craske et al, 2016(Craske et al, , 2019Taylor, Lyubomirsky, & Stein, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a prior metaanalysis suggested that both reward sensitivity and learning rate contribute to performance on the task (Huys et al, 2013), the specific aspects of reward processing that may be gauged by PRT performance remains an important topic for future research. Overall, while research has begun to explore links between subcomponents of reward processing and anhedonia, neurobiological processes through which anhedonia relates to subcomponents of reward remain undercharacterized (Kaya & McCabe, 2019;Treadway & Zald, 2011) | 1227 development efforts focused on reward processing (Craske et al, 2016(Craske et al, , 2019Taylor, Lyubomirsky, & Stein, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…A growing body of literature supports anhedonia and alterations in reward processing as a promising endophenotype for depression (Admon & Pizzagalli, 2015; Hasler, Drevets, Manji, & Charney, 2004; Whitton, Treadway, & Pizzagalli, 2015), although the ways in which anhedonia may relate to differing aspects of reward processing remain unclear (Höflich, Michenthaler, Kasper, & Lanzenberger, 2019; Kaya & McCabe, 2019). Generally, reward processing is now recognized as comprised of several interrelated, but distinct components, including anticipation and motivation to approach rewards (i.e., “wanting”), consumption of rewards (i.e., “liking”), and learning to alter future behavior following receipt of rewards (i.e., “learning”; Berridge, Robinson, & Aldridge, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Much of this work was initially driven by observations that individuals with EDs often endorse increased anhedonia [ 5 , 6 ] outside the context of depression, alongside altered activity in reward-related brain regions to disorder-specific stimuli (i.e., thinness, weight loss, food) [ 7 ]. In addition, recent theoretical work outside of EDs has proposed that because anhedonia appears to be driven by neurobiological alterations in the reward system [ 8 , 9 ], which also appears to be altered in EDs, treatments that target reward-related symptoms and anhedonia may help improve long-term outcomes [ 10 , 11 ]. However, the field’s knowledge regarding specific aspects of hedonic processing has been limited by (a) a lack of consideration of different subcomponents of reward processing that may influence an individual’s ability to experience pleasure and (b) insufficient consideration of anhedonia across a range of ED diagnoses.…”
Section: Introductionmentioning
confidence: 99%
“…To develop new targets for treatment, a fundamental understanding of the mechanisms that underly depression symptoms is needed. Anhedonia, the lack of interest and pleasure in normally rewarding experiences, is one of the main symptoms of depression and is thought to be underpinned by dysfunctional reward processing (Argyropoulos and Nutt, 2013;Treadway and Zald, 2011) (Kaya and McCabe, 2019;McCabe, 2018;Rizvi et al, 2016).…”
Section: Introductionmentioning
confidence: 99%